Propagation and Possible Allelopathic Effects of Vernoniazeylanica on Selected Bioassay Species - Senarathne, S.H.S.; Udumann, S. S. (International Coconut Community Journal, 2020)
Vernonia zeylanica (L.) belongs to the family Asteraceae, is one of the major endemic weed species present in coconut (Cocos nucifera L.) plantations of the tropics, which propagates very easily. There is a possibility that this plant could also possess allelopathic effects, but this has not been scientifically tested. Thus, a study was carried out to determine the seed germination of V. zeylanica under soil moisture stress conditions, shoot propagation methods and possible allopathic effects of this species, on selected species in bioassay tests. Germination of V. zeylanica seeds was not observed at higher osmotic potential (-0.9 MPa). The highest sprouting percentage of this species were obtained with soft wood cuttings. The aqueous leaf extract was highly phytotoxic, and it significantly reduced germination and seedling growth of all bioassay species tested. Full strength (33.3 g L-1) aqueous extracts of leaves significantly reduced the germination percentage, root and hypocotyl growth rates of all species tested. The inhibitory effects were often dependent on concentration. However, the degree of inhibition varied among the test plant species. The seedling emergences of all four tested plants were severally inhibited when planted in V. zeylanica contaminated soil. The results indicated that incorporated aqueous leaf extract of V. zeylanica and its rhizosphere contaminated soil can suppress seed germination, seedling growth and seedling emergence of certain plant species indicating a possible allelopathic effect.